Cytotoxicity of universal dental adhesive systems: Assessment in vitro assays on human gingival fibroblasts. (October 2019) - Pagano, Stefano; Lombardo, Guido; Balloni, Stefania; Bodo, Maria; Cianetti, Stefano; Barbati, Antonella; Montaseri, Azadeh; Marinucci, Lorella
Abstract: Universal adhesives are the most important innovation in restorative dentistry. They are composed of different monomers, solvents and fillers. The potential cytotoxic effect of these materials is an important scientific aspect in recent literature. The aim of this study was to determine, using different in vitro techniques, the cytotoxicity evaluation of seven universal enamel-dental adhesives on human gingival fibroblasts. For this purpose, seven universal dental enamel adhesives have been evaluated by in vitro cytotoxicity tests using direct contact tests (an unpolymerized and a polymerized method) and an indirect contact test: preparation of extracts. The polymerized method showed a cytotoxicity range from 36% (G-PremioBond, GPB) to 79% (FuturaBond M+, FB). With the unpolymerized direct methods the range was from 4% (Prime&Bond Active, PBA) to 40% (Ibond Universal, IB) for undiluted adhesives; generally passing to the major dilutions the test showed a strong inhibitory activity by all the adhesives. Whereas with the indirect method by diluting the extracts of all dental adhesives the cell viability increased. The data obtained from the work has shown a lower cytotoxic effect of Optibond Solo Plus (OB) and Adhesive Universal (AU) with more reliable results with the extracts technique. The choice of reliable in vitro cytotoxic technique could represent, in dental practice, an important aid for clinical procedures in the use of adhesive systems. Graphical abstract: Unlabelled Image Highlights: The evaluation of cytotoxicity is important in the use of universal adhesives The extract methods seemed to be the most reliable in vitro evaluation technique With extract increasing diluitions, the cytotoxic effect of universal adhesives was reduced, with a dose-dependent effect